A non-covalent peptide-based strategy for siRNA delivery. (22nd January 2007) - Crombez, L.; Charnet, A.; Morris, M.C.; Aldrian-Herrada, G.; Heitz, F.; Divita, G.
Abstract : The major obstacle to clinical development of siRNAs (short interfering RNAs), like for most of the nucleic-acid-based strategies, is their poor cellular uptake and bioavailability. Although several viral and non-viral strategies have been proposed to improve siRNA delivery, their applications in vivo remain a major challenge. We have developed a new strategy, based on a short amphipathic peptide, MPG, that is able to form stable nanoparticles with siRNA. MPG-based particles enter the cell independently of the endosomal pathway and can efficiently deliver siRNA in a fully biologically active form into a variety of cell lines and in vivo . This short review will discuss the mechanism and the potency of the MPG strategy for siRNA delivery both in vitro and in vivo .